Immunological reactivity in patients with unstable angina pectoris - Zavalskaya, T.V. (Reports of the National Academy of Sciences of Ukraine, 2014)
The study involved 67 patients with unstable angina pectoris (UAP) aged 55 to 69 years (20 patients with recent onset angina pectoris and 47 patients with progressive angina pectoris) and 22 healthy individuals. Determination of population and subpopulation of lymphocytes was performed by monoclonal antibodies. Determination of immunoglobulins Ig G, Ig A, Ig M, and circulating immune complexes (CIC) in blood serum was performed by the Mancini method. The results showed that immunological changes of patients with UAP manifest by depression of T-cell immunity with the development of T lymphocytes subpopulations imbalance (predominant T-suppressor reduction). UAP patients had humoral immunity activation indicated by an increase of the CIC and Ig G.